Biofilm in combined sewers: wet weather pollution source and/or dry weather pollution indicator? - Rocher, V.; Azimi, S.; Moilleron, R.; Chebbo, G. (Water Science and Technology, 2003)
In a sewer trunk, three kinds of deposit, acting as potential wet weather sources, can be found: the biofilm, the organic layer and the gross bed sediment. This research program, on the ‘‘Le Marais’’ catchment (Paris, France), focused on the biofilm. The objectives were to describe, using a Transmission Electronic Microscope, the architecture of the sewer biofilm and to investigate the contents and the distributions of aliphatic and aromatic hydrocarbons in biofilm. The electron micrographs illustrated a uniform film of bacteria totally covering the surface of a thick organic matrix. A large cohesion of the cell layer and organic matrix complex, due to exopolysaccharides, was noticed. Hence, the hydrocarbon contents were measured not only in the biofilm itself, but in this complex. Our results showed that almost all hydrocarbons were stored in the gross bed sediment and the organic layer and, consequently, the biofilm was not an important potential source of wet weather pollution. Comparison between the hydrocarbon distributions in the biofilm and in the other deposits indicated that the biofilm could be used as an indicator of the aliphatic hydrocarbon pollution in the organic layer.